Keefektifan Metode Contextual Teaching and Learning dalam Menulis Narasi di Sekolah Dasar - Anggraini, Tri Riya; Permanasari, Dian (STKIP PGRI Bandar Lampung, 2020)
The purpose of this study was to find out whether the CTL model was effective in improving the narrative essay writing skills of grade 6 elementary school students. The research design used was a Quasi experimental study. Based on the results of research conducted, it is known that the pretest data of the experimental and control classes are normally distributed and homogeneous. The pretest t-value is smaller than the t-table price (-0.081 <1.647) and the significance (0.935> 0.05), meaning that HO is accepted. This shows that there is no difference in the average score of narrative essay writing skills between the control class and the experimental class at the time of the pretest. Posttest t-count value is greater than t-table price (2.153> 2,000) and significance (0.036 <0.05). Ha was accepted and HO was rejected. Ha accepted means that there is a difference in the average score of narrative essay writing skills between the control class and the experimental class, ie the average experimental class is higher with a mean difference of 0.1552. Large increase in the experimental class can be seen in the average normalized gain of 0.357 or included in the medium category, while the control class 0.209 included in the low category. The effectiveness of the CTL model is expected to be a consideration for grade 6 teachers to apply the CTL model to Indonesian language learning with other aspects or material.